A longitudinal investigation of the predictors of older drivers' speeding behaviour. (August 2016) - Chevalier, Anna; Coxon, Kristy; Rogers, Kris; Chevalier, Aran John; Wall, John; Brown, Julie; Clarke, Elizabeth; Ivers, Rebecca; Keay, Lisa
Highlights: Longitudinal GPS-monitored speeding was examined for 182 drivers aged ≥75 years. Age and lower function predictive of a decrease in speed events. Mileage reduced over time. Speed event involvement may be reduced through driving less. Abstract: There is little objective evidence about the extent older drivers' are involved in speeding or factors that may influence this behaviour. Particular concern exists for the increasing number of older drivers with poor or declining cognitive and visual function. This study investigates whether a reduction in speeding forms part of the self-restrictive driving behaviour evident when older drivers experience poor cognitive and visual function. Driving data over 12 months were collected from 182 volunteers aged 75–94 years. Driving speed was estimated using Global Positioning System location, and speed limit data was based on a service-provider database. Speed events were defined as driving 1 km/h or more, with 3% tolerance, above a single speed limit, averaged over 30 s. Almost all participants (99%) were involved in speed events. While, 16–31% of participants experienced a meaningful decline in cognitive or visual function during the 12-months, these declines were not predictive of a change in speed events. Our results indicate speeding behaviour in this age group was highly prevalent, but less so for the oldest drivers whereby the rate of speed events was 7% lower per year older (IRR = 0.93, 95%CI = 0.89–0.96). Older drivers with worse function were less involved in speed events (unadjusted for distance driven) during 12 months of observation. Weekly distance driven decreased over the year by approximately 0.45 km with every week of monitoring for these older drivers. When distance driven was taken into account, decreased function was not predictive of involvement in speed events, indicating the reduction in speed events may be achieved by older drivers with lower function reducing distance driven. These results are important for developing policy to address speeding behaviour of the growing population of older drivers to reduce the incidence of crashes and resulting casualties.